SOME ASPECTS OF ELECTRON CORRELATION, MAGNETISM, AND LOCALIZATION IN SPATIALLY DISORDERED-SYSTEMS - Logan, D (1991)
We consider a disordered Hubbard model for a system characterized by quenched liquid-like disorder, with correlation treated at the generalized Hartree-Fock level and the possibility of local magnetic moments introduced from the outset. A simple theory based on averaged Green functions is used to describe the properties of the system in the local moment domains in particular, and their evolution with number density and both structural and electronic parameters of relevance. A probabilistically based mean-field theory is then developed to ' address the localization characteristics of the HF pseudoparticle states, and the consequent disorder-induced metal-insulator transition. Three principal density domains of interest are identified: a low density insulator with local magnetic moments, a metallic phase with local moments at intermediate densities, and a higher density nonmagnetic metallic state. The theory is used to provide an interpretation of bulk experiments on expanded fluid alkali elements, with particular emphasis on the insulating and "dirty" metallic domains. © 1991 American Institute of Physics.